New AIM/CIPS global observations of gravity waves near 50–55 km - C. E. Randall; J. Carstens; J. A. France; V. L. Harvey; L. Hoffmann; S. M. Bailey; M. J. Alexander; J. D. Lumpe; J. Yue; B. Thurairajah; D. E. Siskind; Y. Zhao; et al. (Geophysical Research Letters)
Abstract This paper describes a new data set from the Aeronomy of Ice in the Mesosphere (AIM) Cloud Imaging and Particle Size (CIPS) instrument, from which gravity waves (GWs) at an altitude of 50–55 km can be inferred. CIPS is sensitive to GWs with horizontal wavelengths from ~15 to 600 km and vertical wavelengths longer than 15 km. Several examples of GWs in CIPS observations are shown, including waves associated with the Andes Mountains, island topography, convection, the polar night jet, and the tropospheric jet stream. GW signatures in the CIPS data are shown to agree well with near‐coincident but lower altitude measurements from the Atmospheric Infrared Sounder (AIRS) in June of 2016. Results suggest the power of combining CIPS measurements with those from other instruments to investigate GW filtering and propagation. The CIPS data set opens new areas of inquiry, enabling comprehensive investigations of GWs in the middle atmosphere on a near‐global scale.